The House of Hades - Riordan, Rick (New York Disney/Hyperion Books, 2013)
If the five demigods can fight their way through the Gaea's forces, and Percy and Annabeth can survive the House of Hades, then the Seven will be able to seal the Doors of Death and prevent the giants from raising Gaea. But, Leo wonders, if the Doors are sealed, how will Percy and Annabeth be able to escape?
1
Keywords: Monsters -- Fiction; Mythology, Greek -- Fiction; Mythology, Roman -- Fiction; Prophecies -- Fiction